Think-aloud Protocols – A Useful Tool for Investigating the Linguistic Aspect of Translation - Künzli, Alexander (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThink-aloud protocols (TAPs) have often been used to study the cognitive aspect of translation. This paper shows their usefulness for investigating the linguistic aspect of translation. Examples are drawn from material collected in 40 think-aloud sessions over several years. The participants were professional translators or trainee translators. The language pairs involved are French-German and French-Swedish. The translational linguistic problems discussed fall into the following categories: a) grammatical (the interpretation of French participial clauses), b) textual (the use of connectors), c) functional (different realizations of one and the same linguistic function in French on the one hand, and in German and Swedish on the other), and d) sociolinguistic (the rendering of the formal vous into Swedish by the more formal ni or the less formal du).